Dampak Pembelajaran Jarak Jauh Terhadap Kecemasan Orang Tua Murid di Masa Pandemi Covid-19 - Tirajoh, Carissa V; Munayang, Herdy; Kairupan, Bernabas H. R. (UNIVERSITAS SAM RATULANGI, 2021)
Abstract: The COVID-19 pandemic has resulted in all schools implementing distance learning. Distance learning suddenly makes parents and even children not prepare well as a result of problems such as the division of time between work and child supervision while learning takes place, the lack of availability of electronic devices and even family conflicts. This can trigger concern, especially in parents. This concern has an impact on mood swings and thoughts so that parents can issue verbal abuse to their children during lockdown. This study aims to determine the level of anxiety of parents regarding distance learning during the COVID-19 pandemic. This research was made in the form of a literature study which aims to summarize and present more comprehensive facts from various existing literature, in the form of journals and articles on the internet on Google Scholar, PubMed, ClinicalKey. Literature to be used in English and Indonesian, within the last 1 year (2020) and can be accessed in full. Based on the literature reviewed, it was found that distance learning disrupts the lives of parents and creates anxiety. Parents of elementary, middle and high school students felt greater anxiety than those who were already students. The SAS results also showed that 10.8% of parents of primary school children experienced increased anxiety. Keywords: anxiety, parents, online learning, pandemic.Â Â Abstrak: Pandemi COVID-19 ini mengakibatkan seluruh sekolah menerapkan pembelajaran jarak jauh. Pembelajaran jarak jauh yang secara tiba-tiba membuat orang tua bahkan anak-anak tidak mempersiapkan diri dengan baik akibatnya muncul masalah-masalah seperti pembagian waktu antara pekerjaan dan pengawasan anak saat pembelajaran berlangsung, kurangnya ketersediaan perangkat elektronik bahkan konflik keluarga. Hal tersebut bisa memicu kekhawatiran terutama pada orang tua. Kekhawatiran ini berdampak pada perubahan suasana hati dan pikiran sehingga orang tua bisa mengeluarkan kekerasan verbal pada anak-anaknya selama lockdown. Penelitian ini bertujuan untuk mengetahui tingkat kecemasan orang tua murid terhadap pembelajaran jarak jauh di masa pandemi COVID-19. Penelitian ini dibuat dalam bentuk studi kepustakaan yang bertujuan untuk merangkum dan menyajikan fakta yang lebih komperhensif dari berbagai literatur yang telah ada sebelumnya, dapat berupa jurnal dan artikel di internet pada Google Scholar, PubMed, ClinicalKey. Literature yang akan digunakan dalam Bahasa Inggris dan Bahasa Indonesia, dalam jangka waktu 1 tahun terakhir (2020) dan dapat diakses secara penuh. Berdasarkan literature-literature yang direview didapatkan pembelajaran jarak jauh mengganggu kehidupan orang tua dan menimbulkan rasa cemas. Rasa cemas yang dirasakan lebih besar pada orang tua siswa SD, SMP, SMA dibandingkan yang sudah mahasiswa. Hasil SAS juga didapatkan 10,8% orang tua anak sekolah dasar mengalami peningkatan kecemasan.Kata Kunci: kecemasan, orang tua, pembelajaran daring, pandemi